Structure and properties of AlSi/polyester coating - (:unkn) unknown (WILEY, 2004)
Powder coatings, which are formed by plasma spray technique, are being used in industrial applications. Resistance of plastics and their based composite materials to chemicals, solvents, atmospheric conditions, and high impact strength even at low service temperature increases the importance of plastic and plastic based coating applications. In this study, aluminum silicon based polyester (AlSi/polyester) coating was applied by plasma spraying technique with and without intermediate bond layer coat (NiAl). The effect of coating thickness, intermediate bond layer coat, and plasma spraying parameters on bond strength of coating were studied experimentally. The bond strengths of the coatings were determined according to the ASTM C-633-79. Microstructures of the coating were examined by optic microscopy and scanning electron microscopy (SEM), respectively. Obtained results indicated that plasma spraying current rate, coating thickness, and spraying distance were important factors on bond strength of coating. (C) 2004 Wiley Periodicals, Inc.
Keywords: coatings; strength; structure-property relations; adhesion